T Lymphocyte Myosin IIA is Required for Maturation of the Immunological Synapse - Kumari, Sudha; Vardhana, Santosha; Cammer, Michael; Curado, Silvia; Santos, Luis; Sheetz, Michael P.; Dustin, Michael L. (Frontiers in Immunology, 2012)
The role of non-muscle myosin IIA (heavy chain encoded by the non-muscle myosin heavy chain 9 gene, Myh9) in immunological synapse formation is controversial. We have addressed the role of myosin IIA heavy chain protein (MYH9) in mouse T cells responding to MHC-peptide complexes and ICAM-1 in supported planar bilayers - a model for immunological synapse maturation. We found that reduction of MYH9 expression levels using Myh9 siRNA in proliferating mouse CD4+ AND T cell receptor (TCR) transgenic T cells resulted in increased spreading area, failure to assemble the central and peripheral supramolecular activation clusters (cSMAC and pSMAC) and increased motility. Surprisingly, TCR microcluster speed was reduced marginally, however TCR microclusters dissipated prior to forming a cSMAC. TCR microclusters formed in the Myh9 siRNA-treated T cells showed reduced phosphorylation of the Src family kinase activation loop and displayed reduced cytoplasmic calcium ion (Ca2+) elevation. In addition, Myh9 siRNA-treated cells displayed reduced phosphorylation of the Cas-L substrate domain - a force-dependent Src family kinase substrate - which was also observed in control siRNA cells but at higher levels in foci throughout the immunological synapse except the cSMAC. Cas-L exhibited TCR-ligation dependent induction of phosphorylation. These results provide further evidence that T cell activation is modulated by intrinsic force-generating systems and can be viewed as a mechanically responsive process influenced by MYH9.